TWENTIETH CENTURY IN THE DESTINIES OF THE NORTH CAUCASUS INTELLIGENTSIA: I.M. SHAKOV AND HIS DESCENDANTS - I. L. BABICH; Chr. STRAYHORN (Кавказология, 2020)
This article represents the study of the destinies of several generations one of of one of the Kabardian families, Shakov on the basis of two types of sources – state and private archives in France and the Shakov-Strayhorn’ family archive. One of the well-known persons among Adyg’s intelligentsia – doctor Izmail Magometovich Shakov was born in 1878 in Kabarda. He had an excellent career in the Russian Empire. He received a higher medical education, had a medical practice and founded his own clinic in Grozny. He got married, the family had three children. The 1917 revolution changed his life in many ways. He was forced to emigrate with his family to France. The article analyzes the professional and socio-political life of Izmail Shakov in exile, describes his family life in Grozny, Nalchik and Paris. Separately, the authors examine Shakov's social circles in Paris (Muslim, Russian and Caucasian). A granddaughter Fatima was born in Paris, who married an American. The couple moved to the United States where for permanent residence. Since that time, a new page in the life of the Shakovs begins. The great-grandchildren and great-great-grandchildren of the Shakovs, who were born in the United States became Americans. The descendants have lost their Kabardian roots and national and religious identity. The authors analyze the reasons for the current situation.